Safe place by design : the impact of the physical environment on health / Aldrin Abdullah, Massoomeh Hedayati and Mohammad Javad Maghsoodi - Abdullah, Aldrin; Hedayati, Massoomeh; Maghsoodi, Mohammad Javad (2018)
Recent research examining the effect of neighbourhoods on health and well-being has often focused on neighbourhood physical environment. Good living environment is thought to improve health and fear of crime is recognised to be a mediator of the relationship between physical environment and health. Because few studies have investigated this relationship, this study aims to examine the impact of the house quality on fear of crime and health. A total of 230 households from a residential neighbourhood in Malaysia participated in the study. Using structural equation modelling, the findings indicate that housing quality and fear of crime can account for a proportion of the variance in residents‟ self-rated health. However, there is no significant relationship between housing quality and fear of crime. Results also show that fear of crime does not mediate the relationship between housing quality and health in the study area. This study suggests that the environment-fear relationship should be re-examined theoretically.